240‐week entecavir maleate treatment in Chinese chronic hepatitis B predominantly genotype B or C. Issue 10 (6th July 2022) - Xu, Jing‐Hang; Fan, Ya‐Nan; Yu, Yan‐Yan; Si, Chong‐Wen; Zeng, Zheng; Xu, Zhong‐Nan; Li, Jun; Mao, Qing; Zhang, Da‐Zhi; Tang, Hong; Sheng, Ji‐Fang; Chen, Xin‐Yue; et al.
Abstract: This study aimed to evaluate the efficacy and safety of entecavir(ETV) versus ETV maleate in Chinese patients with chronic hepatitis B(CHB). This was a randomized, double‐blind, double‐dummy, controlled, multicentre study. Patients were randomly assigned to receive 48 weeks of treatment with 0.5 mg/day ETV (group A) or 0.5 mg/day ETV maleate (group B), then, all patients received treatment with 0.5 mg/day ETV maleate from week 49 onwards. Patients were regularly followed up. Serum hepatitis B virus (HBV) markers were detected. Adverse events (AE) were recorded. The primary endpoint was the decline in HBV DNA in each group at the end of treatment. Secondary endpoints included the rate of HBV DNA below the lower limit of detection (LLOD) (20 I U/ml) at the end of treatment, the rate of hepatitis B e antigen (HBeAg) loss, the rate of HBeAg seroconversion and serum alanine aminotransferase (ALT) normalization. One hundred and thirty‐seven (71 in group A) patients with HBeAg‐positive CHB and 46 (21 in group A) patients with HBeAg‐negative CHB completed the 240‐week treatment and follow‐up. Baseline characteristics were well balanced between the two groups. For the HBeAg‐positive CHB patients, the mean HBV DNA level had similarly decreased from baseline in both groups (A: by 6.67 log10 IU/ml vs. B: by 6.74 log10 IU/ml; p  > .05) at Week 240. Patients who achieved undetectable levels of serum HBV DNA (<20 IU/ml) at Week 240 were similar between groups (A:91.55% vs. B:87.88%; p  > .05). Both groups achieved similar HBeAg seroconversion rates at week 240 (A:26.98% vs. B:20.97%; p  > .05). Both groups achieved similar normalization of ALT (A:87.32% vs. B:83.61%; p  > .05) at Week 240 ( p  > .05). For the HBeAg‐negative CHB patients, the mean HBV DNA level had similarly decreased from baseline in both groups (A: by 6.05 log10 IU/ml vs. B: by 6.10 log10 IU/ml; p  > .05) at Week 240. Patients who achieved undetectable levels of serum HBV DNA at Week 240 were similar between groups (A:100% vs. B:100%). Both groups achieved similar normalization rates (A:90.91% vs. B: 95.45%; p  > .05) of ALT at Week 240 ( p  > .05). In conclusion, long‐term ETV maleate treatment was safe and efficient in Chinese CHB predominantly of genotype B or C.